EPR Spectroscopy of Different Sol Concentration Synthesized Nanocrystalline-ZnO Thin Films. (22nd November 2015) - Arora, Manju; Zargar, Rayees A.; Khan, S. D.
Abstract : Nanocrystalline zinc oxide (nc-ZnO) thin films were grown on p-type silicon substrate through spin coating by sol-gel process using different sol concentrations (10 wt.%, 15 wt.%, and 25 wt.%). These films were characterized by high resolution nondestructive X-ray diffraction (XRD), scanning electron microscopy (SEM) with energy dispersive X-ray analysis (EDS) attachment, and electron paramagnetic resonance (EPR) techniques to understand variations in structural, morphological, and oxygen vacancy with respect to sol concentration. The film surface morphology changes from nanowall to nanorods on increasing sol concentration. EPR spectra revealed the systematic variation from ferromagnetic to paramagnetic nature in these nc-ZnO films. The broad EPR resonance signal arising from the strong dipolar-dipolar interactions among impurity defects present in nc-ZnO film deposited from 10 wt.% sol has been observed and a single strong narrow resonance signal pertaining to oxygen vacancies is obtained in 25 wt.% sol derived nc-ZnO film. The concentrations of impurity defects and oxygen vacancies are evaluated from EPR spectra, necessary for efficient optoelectronic devices development.